Experimental Research on Rubble Stone Masonry Walls - Pinho, Fernando Farinha da Silva (2017)
This research was developed in the Structural Laboratory of DEC-FCT/UNL, and the first author was supported by a scholarship through the Program 2/5.3/PRODEP/2002. The authors are grateful to the following industrial companies, which sponsored the majority of the experimental work: Grupo Edifer; Secil Outão, SA; Secil Martingança, Lda; Lusical, SA; Tecnasol-FGE, SA; Betopal, SA; Tecnima-Enerpac; Betão LIZ, SA; SPGO Lda; Cimianto, SA; Lusoceram, SA; Construtora do Infantado, Lda; Ensul, SA; SIKA Portugal, SA; Degussa -Bettor MBT, SA; Codimetal, SA; Vimaplás, Lda; Fradical, Lda; Dywidag, SA; Parapedra, Lda; Somator, Lda; J. Piteira, Lda and F. F. Caçador, Lda.